Endocrine disruption rewards: bisphenol-A-induced reproductive toxicity and the precision ameliorative potential of flavonoids in preclinical studies. A systematic review and meta-analysis - Okon, Michael Ben; Fasongbon, Ilemobayo Victor; Swase, Dominic; Dangana, Reuben Samson; Makena, Wusa; Ojiakor, Vivian Onyinye; Etukudo, Ekom Monday; Chebet, Joan; Musyoka, Angela Mumbua; Ifie, Sandra Etumah; Mbyemeire, Herbert; Mbina, Solomon Adomi; et al. (Frontiers in Toxicology, 2025)
IntroductionBisphenol A (BPA), a pervasive endocrine-disrupting chemical, impairs male reproductive health via oxidative stress, hormonal dysregulation, and hypothalamic–pituitary–gonadal (HPG) axis disruption. Flavonoids, widely present in plant-derived foods and medicinal herbs, possess antioxidant and steroidogenic modulatory properties that may counteract BPA toxicity, yet preclinical findings remain inconsistent. This study aims to systematically evaluate and quantitatively synthesize preclinical evidence on the protective effects of flavonoids against BPA-induced male reproductive toxicity.MethodsUsing PRISMA 2020 guidelines, Web of Science, Scopus, and PubMed were searched up to September 2024. Eligible studies involved BPA exposure in male rodents with flavonoid co-treatment and reported reproductive endpoints. Hormonal and oxidative stress biomarkers were pooled using a random-effects model, expressed as standardized mean differences (SMDs), with heterogeneity assessed by I2 statistics. Twenty studies were included.ResultsBPA significantly reduced testosterone (SMD = −4.91), estradiol (SMD = −2.72), follicle-stimulating hormone (FSH) (SMD = −7.71), and luteinizing hormone (SMD = −5.54), while increasing malondialdehyde and reducing antioxidant enzymes (SOD, CAT, GPx, and GSH).DiscussionFlavonoid co-treatment significantly improved hormonal profiles and oxidative balance, with the greatest recovery in FSH. High heterogeneity (I2 > 84%) reflected variability in doses, treatment duration, compound purity, and species. Flavonoids exhibit marked ameliorative potential against BPA-induced reproductive toxicity in preclinical models, largely through hormonal regulation and oxidative stress mitigation. Standardized protocols and dose–response studies are essential to enhance reproducibility and translational relevance.